Five‐year effectiveness of bariatric surgery on disease remission, weight loss, and changes of metabolic parameters in obese patients with type 2 diabetes: A population‐based propensity score‐matched cohort study. Issue 3 (7th January 2020) - Wu, Tingting; Wong, Simon Kin Hung; Law, Betty Tsz Ting; Grieve, Eleanor; Wu, Olivia; Tong, Daniel King Hung; Leung, David Kai Wing; Lam, Cindy Lo Kuen; Wong, Carlos King Ho
Abstract: Aims: To compare disease remission rates, weight loss, and changes of metabolic parameters of patients after bariatric surgery with nonsurgical patients. Methods: Based on the 2006‐2017 Hospital Authority database, a population‐based retrospective cohort of obese type 2 diabetes mellitus (T2DM) patients with and without bariatric surgery were identified. Surgical patients were matched with nonsurgical patients on 1‐to‐5 propensity score. Remission rates of diabetes, hypertension, and dyslipidaemia were reported annually up to 60 months. Changes in weight loss measurements (Body Mass Index [BMI], percentage of total weight loss [%TWL], percentage of excess weight loss [%EWL], and percentage of rebound in excess weight loss [%REWL]) and metabolic parameters (haemoglobin A1c [HbA1c ], systolic blood pressure [SBP], diastolic blood pressure [DBP], and low‐density lipoprotein cholesterol [LDL‐C]) were measured for both groups. Results: Four hundred one surgical patients (310 restrictive surgeries; 91 bypass surgeries) and 1894 nonsurgical patients were included. Surgical patients had higher remission rates in diabetes and dyslipidaemia and better glycaemic control at 12 to 60 months (all P s < .01). SBP and DBP were significantly lower for surgical group up to 12 months and similar between two groups after 12 months. Surgical patients had significantly lower BMI during follow‐up period. %TWL and %EWL were higher in the surgery group (15.7% vs 3.7%; 48.8% vs 12.0%) at 60 months ( P < .001); differences in %REWL between two groups were insignificant. The effectiveness of restrictive and bypass surgeries was similar at 60 months, although restrictive surgeries were slightly more effective in T2DM remission. Conclusions: Bariatric surgery was effective in weight loss, remission of diabetes, and dyslipidaemia in 5‐year post‐surgery.